The sequencing of adverbial clauses of time in academic English: Random forest modelling - Rezaee, Abbas Ali; Golparvar, Seyyed Ehsan (Journal of Language Modelling, 2016)
Adverbial clauses of time are positioned either before or after their associated main clauses. This study aims to assess the importance of discourse-pragmatics and processing-related constraints on the positioning of adverbial clauses of time in research articles of applied linguistics written by authors for whom English is considered a native language. Previous research has revealed that the ordering is co-determined by various factors from the domains of semantics and discourse-pragmatics (bridging, iconicity, and subordinator) and language processing (deranking, length, and complexity). This research conducts a multifactorial analysis on the motivators of the positioning of adverbial clauses of time in 100 research articles of applied linguistics. The study will use a random forest of conditional inference trees as the statistical technique to measure the weights of the aforementioned variables. It was found that iconicity and bridging, which are factors associated with discourse and semantics, are the two most salient predictors of clause ordering.